2011
DOI: 10.1103/physreve.83.016304
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent front speed in the Fisher equation: Dependence on Damköhler number

Abstract: Direct numerical simulations and mean-field theory are used to model reactive front propagation in a turbulent medium. In the mean-field approach, memory effects of turbulent diffusion are taken into account to estimate the front speed in cases in which the Damköhler number is large. This effect is found to saturate the front speed to values comparable with the speed of the turbulent motions. By comparing with direct numerical simulations, it is found that the effective correlation time is much shorter than fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…The term [49], where a reactive front propagation in a turbulent flow was studied using the Kolmogorov-Petrovskii-Piskunov-Fisher equation. To describe the interaction with a turbulent velocity field an advection term was added to this equation, so that advection-reaction-diffusion equation reads [49]:…”
Section: Turbulent Transport Of Admixtures and Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The term [49], where a reactive front propagation in a turbulent flow was studied using the Kolmogorov-Petrovskii-Piskunov-Fisher equation. To describe the interaction with a turbulent velocity field an advection term was added to this equation, so that advection-reaction-diffusion equation reads [49]:…”
Section: Turbulent Transport Of Admixtures and Temperaturementioning
confidence: 99%
“…This equation has also been amended by an advection term to describe the interaction with a turbulent velocity field [52,53]. In MFS of [49] memory effects of turbulent diffusion have been taken into account to determine the front speed in the case when the turbulent time, τ 0 , is much larger than the characteristic chemical time, τ c . It was found that the memory effects saturate the front speed to values of the turbulent speed, while the nonlinearity of the reaction term increases the front speed.…”
Section: Introductionmentioning
confidence: 99%
“…From our numerical simulations, we find that H is negligible. We further assume: (a) the turbulence time scales are smaller than the scales associated with the front so that the time variation of the turbulent fluctuations in the velocity field can be ignored in the evolution equation for F ; (b) isotropic velocity field vv = v 2 I; and (c) the τ approximation vv · ∇c = vc /τ [17]. Then from Eq.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Using the procedure outlined in Ref. [17], we now briefly describe the methodology to obtain the eddy diffusivity for model A. Assuming very small variations of the concentration field perpendicular to the direction of front propagation, we decompose these as c(x, y) = c(x) + c (x, y).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation